2022
DOI: 10.1093/neuonc/noac234
|View full text |Cite
|
Sign up to set email alerts
|

Neurological applications of belzutifan in von Hippel-Lindau disease

Abstract: Von Hippel Lindau (VHL) disease is a tumor predisposition syndrome caused by mutations in the VHL gene that presents with visceral neoplasms and growths, including clear cell renal cell carcinoma, and central nervous system manifestations, such as hemangioblastomas of the brain and spine. The pathophysiology involves a dysregulation of oxygen sensing caused by inability to degrade HIFα, leading to overactivation of hypoxic pathways. Hemangioblastomas are the most common tumors in patients with VHL and cause si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…The optimization efforts yielded alkyloxy-substituted cyclopenta­[ c ]­thiophenes with exquisite activity in cellular assays, which are the first examples of HIF-2α inhibitors devoid of two linked aromatic rings, a structural motif that was considered obligatory for potent inhibition of HIF-2α to date. Diversifying the available chemotypes for HIF-2α inhibitors is desirable, as it was reported that prolonged treatment with aryloxy-2,3-dihydro-1 H -inden-1-ol derivatives resulted in the acquisition of resistance in patients with ccRCC. Crystallographic data confirmed that this new chemotype is able to present key pharmacophoric elements in the hydrophobic cavity in such a way that perturbation of key amino acids is appropriately induced. The optimization efforts resulted in the discovery of compound 35r , which exhibited a significant target modulation in tumors in vivo in mice.…”
Section: Discussionmentioning
confidence: 99%
“…The optimization efforts yielded alkyloxy-substituted cyclopenta­[ c ]­thiophenes with exquisite activity in cellular assays, which are the first examples of HIF-2α inhibitors devoid of two linked aromatic rings, a structural motif that was considered obligatory for potent inhibition of HIF-2α to date. Diversifying the available chemotypes for HIF-2α inhibitors is desirable, as it was reported that prolonged treatment with aryloxy-2,3-dihydro-1 H -inden-1-ol derivatives resulted in the acquisition of resistance in patients with ccRCC. Crystallographic data confirmed that this new chemotype is able to present key pharmacophoric elements in the hydrophobic cavity in such a way that perturbation of key amino acids is appropriately induced. The optimization efforts resulted in the discovery of compound 35r , which exhibited a significant target modulation in tumors in vivo in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Anemia is the most common adverse effect. Although long-term results are not known, these treatments represent an interesting option [42,46,47].…”
Section: Recommendations Regarding Patient Managementmentioning
confidence: 99%
“…[ 11 , 12 ] The surgical efficacy of sporadic and cystic hemangioblastoma is relatively satisfactory, while the treatment of solid, familial, and multiple HB is still difficult, especially when located in the brainstem and spinal cord. [ 13 ]…”
Section: Introductionmentioning
confidence: 99%
“…[11,12] The surgical efficacy of sporadic and cystic hemangioblastoma is relatively satisfactory, while the treatment of solid, familial, and multiple HB is still difficult, especially when located in the brainstem and spinal cord. [13] If there is edema around hemangioblastoma, it is easy to be misdiagnosed as brain metastasis on MRI. Recently, a case of cerebellar hemangioblastoma simulated brain metastasis shown by magnetic resonance imaging was admitted to our hospital, which is reported as follows.…”
Section: Introductionmentioning
confidence: 99%